Шпиндельний вузол з електромеханічним затискним механізмом - Недобой, Вадим Анатолійович (НТУ "ХПІ", 2015)
В роботі представлений мотор-шпиндель з електромеханічним затискним механізмом зібраний на основі модульного принципу на базі мотор-шпинделя. Дані його параметри та основні технічні характеристики. Представлена можливість використання мотор-шпинделя у двох варіантах: з використання без модуля з електромагнітною муфтою та з модулем–для розмикання моменту на затискний механізм. Також показані його основні складові вузли та їх компоновка та елементи управління мотор-шпинделем і приводом затиску. Розглянута структурна схема мотор-шпинделя для обох варіантів. Дані рекомендації по майбутніх експериментальних дослідженнях.

The paper presents the motor-spindle with electromechanical clamping mechanism is assembled on the basis of the modular principle on the basis of the motor-spindle. The basis is ready module motor-spindle, which is the standard unit, and interchangeable modules are driven clamping and clamping chuck, that increasing its technical and economic indicators. Give options and basic technical specifications. Presents the use of the motor-spindle in two variants: without the use of a module with an electromagnetic clutch and with module-for tripping of torque on the clamping mecha-nism. It also shows the key building components and their arrangement and controls elements the motor-spindle and drive clamping mechanism. Also indicated its standard components that are unified. Considered structural diagram of the motor-spindle for both options and elements of interaction be-tween its parts. Recommendations are given for future experimental and theoretical studies.
Spindle unit with electromechanical clamping mechanism
Keywords: мотор-шпиндель; привод затиску; модульний принцип; затискний патрон; motor-spindle; electromechanical clamping mechanism; drive clamp; modular principle